2021
DOI: 10.3390/healthcare9070807
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Postpartum Depression in Adolescents Who Delivered during COVID-19 Social Restrictions: The Experience of a Tertiary Hospital from Bucharest, Romania

Abstract: In the context of the viral spread of COVID-19 in 2020, Romanian authorities declared national confinement for two months. Our country faces a public health issue regarding adolescent pregnancy. This study assessed the predisposition of teenage mothers to postpartum depression and the influence of the viral pandemic on their emotional status. This study enrolled patients 10 to 19 years old who delivered in our department between March–December 2020. Teenagers were attributed to the “lockdown group” (n = 30) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Anxiety can be related to various aspects of a pregnancy, such as changes in the woman's body, need for familial and social adaptation, prenatal procedures and investigations, and preparation for the process of birth. Anxiety is, therefore, frequently encountered in perinatal population and is related to postpartum depression [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety can be related to various aspects of a pregnancy, such as changes in the woman's body, need for familial and social adaptation, prenatal procedures and investigations, and preparation for the process of birth. Anxiety is, therefore, frequently encountered in perinatal population and is related to postpartum depression [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The first reported lower parental stress and postpartum depression (PPD) during the pandemic than before it started, attributed to a life skills program (LSP) and continuous school contact (Astle et al, 2021). The second research project reported a low level of PPD associated with good family support in two groups of adolescent mothers: under lockdown vs. not under lockdown (Matei et al, 2021), while the third found a higher proportion of PPD and lower social support among adolescent than adult mothers in the group (Sangsawang & Sangsawang, 2023).…”
Section: Introductionmentioning
confidence: 98%
“…The family and, especially, the mother, who each have their own belief systems in the sociocultural context of Romania are sometimes on alert if the newborn has problems. 27 …”
Section: Introductionmentioning
confidence: 99%
“…26 The family and, especially, the mother, who each have their own belief systems in the sociocultural context of Romania are sometimes on alert if the newborn has problems. 27 "Newborn at risk" refers to a child exposed to maternal risk factors such as poverty, smoking, alcohol and/or drug use, malnutrition, disease, obstetric history (for example, women with a history of perinatal death, especially early neonatal death, miscarriages, and stillbirths), and being a mother under 16 or over 35 years of age. 28 The fetal risk factors for newborns include prematurity, postmaturity, intrauterine growth restriction, macrosomia, presentation abnormalities, cardiac arrhythmias, oligohydramnios or polyhydramnios, and hyperreactivity.…”
Section: Introductionmentioning
confidence: 99%